생물자원의 논 잡초 생물학적 방제 효과와 그에 따른 수서동물과 곤충 종수 및 벼 수량 변화 - 최효정; Hyo Jung Choi; 서상영; Sang Young Seo; 최선우; Seon U Choi; 이창규; Chang Kyu Lee; 엄미정; Mi Jeong Uhm; 김주희; Ju Hee Kim; et al. (Hanguk hwangyeong nonghak hoeji, 2023)
Golden apple snails (Pomacea canaliculat) (GAS) are widely used for weed control in rice cultivation. However, concerns on the ecological risk of invasive GAS species are increasing. This study aimed to evaluate the overall impacts of GAS on weed control, abundance of aquatic animals and insects, and rice yield, in comparison with that from other biocontrol agents such as loach (Misgurnus mizolepis) and catfish (Silurus asotus), which are alternatives for biological weed control in rice paddy cultivation. Field experiments included five treatments; control, herbicide, GAS, loach, and catfish. During the rice growth, weed appearance and biological abundance were monitored, and at harvest, the rice yield was determined. Weed control efficiency was the highest for GAS treatment (100%), followed by that for herbicide (95.8%), loach (57.5%), and catfish treatments (31.7%). Insect abundance was considerably decreased in GAS treatment due to heavy weed removal, which affects the habitat of aquatic animals and insects. The amount of rice yield (unit: kg 10 a -1 ) was in the order of GAS (798.9) > loach (708.1) = herbicide (700.7) > catfish (629.4) > control (496.0). Therefore, considering the weed control efficiency, biological abudance, and rice yield, loach could be a potential alternative for biological weed control in organic rice farming. However, the activity of the biocontrol agents are susceptible to environmental conditions; therefore, further studies under different conditions are essential to confirm these findings.